DIMENSI TEGAKAN NYAWAI (Ficus variegata Blume) PADA JARAK TANAM YANG BERBEDA DI KHDTK RIAM KIWA KALIMANTAN SELATAN - Finthihani Yumna Ayuningtyas; Yusanto Nugroho; Damaris Payung (Jurnal Sylva Scienteae, 2020)
One effort to increase crop productivity is to pay attention to the appropriate spacing. Using different spacing, the light intensity will be different, as a result it will affect plant growth. Based on this background, the author tries to examine the dimensions of the stands and roots of Nyawai at various spacing with the same age and treatment conditions, so that later it can be used as a planting reference for Nyawai with optimal growth.The spacing treatment used in this study was 2x2m, 3x3m and 4x4m, 6 observation plots as replications. Observation variables are diameter breast height (dbh), height and width of the crown.Keywords: Ficus; Nyawai; Dimentional of Stand; Plant Spacing